Fibrillary deposits: amyloids and tactoids - Looi, Lai Meng (College of Pathologists, Academy of Medicine Malaysia, 1995)
Two forms of abnormal fibrillary protein deposition are considered: amyloidosis and fibrillary (immunotactoid) glomerulonephritis. Amyloid is characterised by an antiparallel, beta-pleated configuration which imparts to it a unique apple-green birefringence after Congo red staining. Inspite of its fairly constant physical properties, the chemical composition of amyloid fibrils is amazingly diverse, encomposing AA protein, light chain fragments, transthyretin, procalcitonin, islet amyloid polypeptide, atrial natriuretic peptides, beta-amyloid protein, beta-2-microglobulin, cystatin C, gelsolin, apolipoprotein A1, lyzozyme and their mutant variants. Amyloid P component and heparan sulphate proteoglycan are ubiquitous non-fibrillary amyloid components which have significant roles in the amyloidogenetic process, as do also precursor fibril proteins. Different amyloid fibril proteins relate to different amyloidosis syndromes and different histological patterns, and provide the basis for new diagnostic approaches to this disorder. Glomerular deposits in fibrillary glomerulonephritis (FGN), although often mistaken for amyloid, differ from it in its negative Congophilia, wider fibril width and highly organised, microtubular-tactoidal appearance ultrastructurally. FGN is essentially a primary glomerulopathy resulting in progressive renal failure. Despite certain differences, intriguing similarities between both entities of fibrillary deposition pose a challenge to researchers as to the mechanisms of abnormal protein crystallization and fibril formation in tissues.